The Contribution of Ulama and Umara in the Development of Islamic Education in the Sultanate of Palembang Darussalam - Maryamah; Alimron; Irja Putra Pratama; Purnomo, Eko (Pascasarjana Universitas KH. Abdul Chalim, 2025)
This article aims to obtain information regarding the contribution of ulama and umara in the development of Islamic education in the Sultanate of Palembang Darussalam. The research method used is descriptive and qualitative analysis with a historical approach, namely by collecting library data from various written sources so that the discussion is carried out qualitatively or using textual descriptions and writing and searching for obtained data through documents, especially documents written in scientific papers. These sources can be accessed through various means, such as libraries and online media. The results of the research show that synergistic intellectual collaboration between ulama and umara produced many written works in the form of religious books in various fields of science, such as fiqh, tauhid, Tarikh, ulumul Qur'an, Sufism, and other Malay books. During the reign of three sultans, a prominent scholar emerged and had a scientific reputation in the field of Ushuluddin science, namely Faqih Jalaluddin. During the reign of Sultan Mahmud Badaruddin Jayo Wikramo, a brilliant scholar named Sheikh Sihabuddin bin Abdullah Muhammad emerged. A charismatic cleric who was also a relative of the Palembang palace, namely Kemas Fakhruddin, also appeared during the reign of Sultan Ahmad Najamuddin I. Meanwhile, a very productive great cleric named Sheikh Abdul Shamad al-Palimbani emerged and became popular during the reign of Sultan Muhammad Bahauddin. The sultanate's role was huge in developing Islamic education by supporting intellectual traditions to produce qualified scholars with a high scientific reputation in the Islamic religion.